Rwanda Climate Services for Agriculture project demonstrates significant productivity, income, food security and women’s empowerment benefits for more than 110,000 participating farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Evaluation shows that the 111,835 farmers, across all 30 districts, who participated in Rwanda Climate Services for Agriculture (RCSA) communication and capacity development interventions were more likely to act on weather and climate information; experienced an average 24% increase in the value of crop production and 30% increase in income from crops; and perceived improvements in food security, investment in farming, coping capacity, and confidence as farmers. Project interventions increased women’s participation in household decision-making and standing in their communities.